2022
DOI: 10.3389/fphar.2022.1033069
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis sativa L. alleviates loperamide-induced constipation by modulating the composition of gut microbiota in mice

Abstract: MaZiRenWan (MZRW) is the most frequently used Traditional Chinese Medicine formula to treat chronic constipation, Cannabis sativa L. is regarded as a monarch drug in MZRW. However, the targets of Cannabis sativa L. that enhance colonic motility and improve constipation symptoms remain unknown. This study was designed to investigate the laxative effect and underlying mechanism of the water extract of Cannabis sativa L. (WECSL) using a loperamide-induced constipation mouse model. We found that WECSL treatment si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Humans have searched for many natural products from edible and medicinal plants that are effective in preventing and treating FC. Modern scientific research has confirmed the laxative effect of M. oleifera leaves ( Li R. et al, 2022 ; Li C. et al, 2022 ; Li L. et al, 2022 ), but the mechanism of the laxative effect of M. oleifera leaves is not yet systematically understood. MOAE was found to be low in fat and high in protein and carbohydrates and contained a certain amount of polysaccharides ( Supplementary Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humans have searched for many natural products from edible and medicinal plants that are effective in preventing and treating FC. Modern scientific research has confirmed the laxative effect of M. oleifera leaves ( Li R. et al, 2022 ; Li C. et al, 2022 ; Li L. et al, 2022 ), but the mechanism of the laxative effect of M. oleifera leaves is not yet systematically understood. MOAE was found to be low in fat and high in protein and carbohydrates and contained a certain amount of polysaccharides ( Supplementary Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cannabis sativa L. aqueous extracts significantly elevated the abundance of B. spp. while relieving constipation ( Li R. et al, 2022 ; Li C. et al, 2022 ; Li L. et al, 2022 ). Our correlation analysis results also support the idea that Butyricoccus might play a beneficial role in the process of FC mitigation by MOAE.…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate is the main source of metabolic energy in the large intestine, helping to maintain its integrity, control intestinal inflammation, and support genomic stability (21). According to reports, butyric acid directly stimulates colon motility by stimulating the release of 5-HT or promoting the cholinergic pathway (22). Recent studies have shown that the gut microbiota acts on intestinal chromaffin cells using SCFAs as mediators, regulating the synthesis and release of 5-HT.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models and human crosssectional studies have successfully demonstrated alterations in gut microbiota caused by phytocannabinoid exposure. More importantly, inflammatory markers and clinical symptoms were improved after correction of the pathologic dysbiosis in animal models (33)(34)(35).…”
Section: Drugs and Bugs: Cannabinoids And Gut Microbiomementioning
confidence: 97%